Teknik Modeling Untuk Meningkatkan Keterampilan Sosial Anak Autis - Safitri, Yona; Marlina, Marlina (Jurnal Penelitian Pendidikan Khusus, 2022)
This research was motivated by the existence of problems in autistic children in class XII at SLB N 2 Padang, who experienced problems in children’s social skills. Social skills are very influential in daily interactions, both interations with the school environment, place of residence and so on as a form of way to get information. This research was conduted with the aim of improving the social skilss of autistic children through modeling techniques at SLB N 2 Padang. This type of research is an experimental method with the study, nami9ely the A-B-A design with the single subject research (SSR) method and target behavior, namely improving social skills on the subject of autistic children, by treating children who like to be alone, cannot play with their friends, lack reciprocal social and emotional relationships. The data obtained in this study is through the ability test instrument with observation and documentation techniques. The results of data analysis from the conditions of phase A1 Phase B, and Phase A2 are decribed in graphical form. The results of this study indicate that the modeling technique is effective for improving social skills for autistic children in class XII at SLB N 2 Padang, which is seen from the results of data analysis under conditions and between conditions.